Recognising False Anomalies in Drillhole EM - Morland R (The Australasian Institute of Mining and Metallurgy, 1994)
In the course of an exploration program aimed at increasing Pasminco Mining's ore reserves, an electromagnetic survey down one of the underground drillholes at the North Mine, Broken Hill, recorded a broad and persistent response. This paper demonstrates that the anomaly was not due to any geological feature, but rather was caused by 'self-response' of the sensing probe. The observed results are due to the surveyed hole lying within a resistive environment and having distinct, but not unusual, changes in dip.This phenomenon has not been widely reported and we believe that there are likely to be similar cases in company records where very genuine looking responses are due to self-response rather than sulphides. These false anomalies can be recognised by correlating the observed data with the calculated down-hole component of the transmitting loop's primary field.